2019
DOI: 10.2135/cropsci2018.08.0485
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Biochar Effects on Wheat Productivity under Arid Conditions

Abstract: Urea is an important source of inorganic N under wheat (Triticum aestivum L.) production system in Multan, Pakistan. However, the average N loss is high, ranging from 22 to 53% of applied N, which poses adverse environmental impacts. Reduced tillage and combined application of biochar and optimal N fertilizer could improve wheat productivity and reduce N losses. We evaluated the effects of two tillage (conventional and reduced tillage), two biochar (no biochar and poultry waste biochar), and three inorganic N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Reduced tillage had been reported to improve soil physical properties, such as bulk density, porosity, penetration resistance, water content, aggregate stability, mean weight diameter, dispersion ratio, root penetration, and water and air permeability (Malecka et al, 2012;Celik et al, 2012;Acar et al, 2018). Also, increased crop residue by reduced tillage has been reported (Shahzad et al, 2019), to keep the soil surface cool and reduce soil temperature and loss of water by evaporation. These effects subsequently leads to increased water use efficiency of the crop (Blanco-Canqui et al, 2017;Obour et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced tillage had been reported to improve soil physical properties, such as bulk density, porosity, penetration resistance, water content, aggregate stability, mean weight diameter, dispersion ratio, root penetration, and water and air permeability (Malecka et al, 2012;Celik et al, 2012;Acar et al, 2018). Also, increased crop residue by reduced tillage has been reported (Shahzad et al, 2019), to keep the soil surface cool and reduce soil temperature and loss of water by evaporation. These effects subsequently leads to increased water use efficiency of the crop (Blanco-Canqui et al, 2017;Obour et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As previously noted, most of the initial soil nutrients were above the low threshold of the soil test classification for corn by the University of Georgia Extension (Table 2) (UGA-AESL, 2023), which likely supplied a good amount of nutrients to the crop by the V5 to V7 growth stage. Moreover, the mineralization of the previous crop residues could have supplied additional nutrients (Shahzad et al, 2018(Shahzad et al, , 2019aSintim et al, 2015;Torma et al, 2018) to meet the demand for the crop by the V5 to V7 growth stage, especially for P where the initial soil P was low at both locations. Torma et al (2018) observed that 2-24 kg ha −1 of P could be supplied to the soil by crop residues.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar from fruit peels and milk tea waste improved bread wheat growth and grain yield as well as soil fertility status in a field study ( Sial et al, 2019 ). Shahzad et al (2019) observed that biochar application increased bread wheat grain yield, protein content, and total nitrogen uptake compared with plots with no biochar, but they also underpinned that reduced tillage was much more economically profitable than biochar application. Under greenhouse conditions, Bista et al (2019) reported that biochar amendment at rates up to 22.4 Mg ha –1 increased wheat shoot and root biomass, independent of the addition of fertilizer, while a double biochar application rate determined a biomass reduction, particularly under fertilized conditions.…”
Section: Introductionmentioning
confidence: 97%